The Unique Role and Contribution of Peer Supporters to MAiD in Canada: Lessons Learned from a National Discussion Series - de Bie, Lee; Dunning, Allison; Theodorou, Allyson; Sinding, Christina; Hawke, Lisa (Canadian Journal of Bioethics / Revue canadienne de bioéthique)

(untitled) (Programmes de bioéthique, École de santé publique de l'Université de Montréal, 2025)
This paper describes lessons learned from a 2024-2025 national discussion series. Peer supporters from across the country came together virtually to discuss the special and important role they play in conversations, care, and policy related to medical assistance in dying (MAiD), building on unique values, standpoints, lived experiences, and ways of being in relationship that are distinct from those of regulated health professionals and informal support networks. We recommend that people exploring MAiD should be offered — and have access to — peer support, if desired, and that peer support programs be properly resourced to provide authentic emotional and love labour that honours a peer support vision for self-determination.